Combination therapy based on nano codelivery for overcoming cancer drug resistance - Hairui Wang; Yongzhuo Huang (Elsevier, 2020)
Multidrug resistance (MDR) has long been a major obstacle in the treatment of malignant tumors. Combination therapy provides a viable and promising strategy to overcome MDR. This article discusses the advantages of nano-based combination therapy and proposes a 3R delivery principle (right place, right time, and right dose) as a reference for development of cancer nanomedicine containing drug combinations. The article also reviews the strategies of nano-based codelivery, with emphasis on the techniques designed to overcome chemoresistance, enhance drug targeting delivery, and reduce immunosuppression.